Access to highly substituted oxazoles by the reaction of α-azidochalcone with potassium thiocyanate - Harisha, Mysore Bhyrappa; Dhanalakshmi, Pandi; Suresh, Rajendran; Kumar, Raju Ranjith; Muthusubramanian, Shanmugam (Beilstein Journal of Organic Chemistry, 2020)
The reactivity of α-azidochalcones has been explored for the preparation of highly substituted oxazoles via a 2H-azirine intermediate. The azidochalcones, when treated with potassium thiocyanate in the presence of potassium persulfate, lead to 2,4,5-trisubstituted oxazoles in good yields. Incidentally, 2-aminothiazoles are the products when ferric nitrate is employed instead of persulfate in the above reaction.
Keywords: aminothiazole; oxazole; potassium persulfate; thiazole; vinyl azide